Capturing the costs of acute hand and wrist injuries: Lessons learnt from a prospective longitudinal burden of injury study. (December 2020) - Robinson, Luke Steven; Brown, Ted; O'Brien, Lisa
Introduction: Given the high incidence of hand and wrist injuries, they are exceptionally costly to the economy. This prospective, longitudinal study aimed to establish methods for capturing the burden of acute hand and wrist injury from an individual and societal perspective. Methods: A prospective longitudinal design with baseline measures of injury type and severity, and repeated measures of disability, cost, and activity limitations and participation restrictions at six weeks, three months, and six months was selected. Participants were recruited from two large urban Australian public health care services. We sought to establish methods for capturing the burden of acute hand and wrist injury from an individual and societal perspective and compare survey completion by the method of administration. Results: A total of 206 patients consented to participate in this study, representing 54% of those invited to participate. The survey completion rates were 18% at six weeks, 2.4% at twelve weeks, and 0.004% at six months following injury. From the limited data collected at six weeks, it was noted that nearly half of the patients reported a decrease in usual financial income, 14% reported absenteeism, and 62% reported presenteeism. Participants who elected to have data collected via phone call had the highest survey completion rate ( n = 6/10; 30%) at six-week's follow-up. Discussion: The study findings highlight the difficulties of completing longitudinal survey research investigating individual and societal burden with this population. Future research should be carefully designed to encourage participation and retention by considering patient and public involvement in study design, the time burden placed on the participants within and across selected survey time points, providing participants with incentives to participate, and highlighting the relevance and real-world applications of the findings.